The translation of non-canonical open reading frames controls mucosal immunity - Jackson, Ruaidhrí; Kroehling, Lina; Khitun, Alexandra; Bailis, Will; Jarret, Abigail; York, Autumn G.; Khan, Omair M.; Brewer, J. Richard; Skadow, Mathias H.; Duizer, Coco; Harman, Christian C. D.; Chang, Lelina; et al. (Nature (London), 2018)
The annotation of the mammalian protein-coding genome is incomplete. Arbitrary size restriction of open reading frames (ORFs) and the absolute requirement for a methionine codon as the sole initiator of translation have constrained the identification of potentially important transcripts with non-canonical protein-coding potential 1 , 2 . Here, using unbiased transcriptomic approaches in macrophages that respond to bacterial infection, we show that ribosomes associate with a large number of RNAs that were previously annotated as ‘non-protein coding’. Although the idea that such non-canonical ORFs can encode functional proteins is controversial 3 , 4 , we identify a range of short and non-ATG-initiated ORFs that can generate stable and spatially distinct proteins. Notably, we show that the translation of a new ORF ‘hidden’ within the long non-coding RNA Aw112010 is essential for the orchestration of mucosal immunity during both bacterial infection and colitis. This work expands our interpretation of the protein-coding genome and demonstrates that proteinaceous products generated from non-canonical ORFs are crucial for the immune response in vivo. We therefore propose that the misannotation of non-canonical ORF-containing genes as non-coding RNAs may obscure the essential role of a multitude of previously undiscovered protein-coding genes in immunity and disease. In mouse macrophages, a range of short and non-ATG-initiated open reading frames that can generate proteins are identified, one of which is shown to be essential for host immunity to enteric mucosal infection and inflammation.